The cinema as model for Spanish popular music in the 80´s. - Rodríguez Centeno, Juan Carlos (Historia y Comunicación Social, 2014)
One of the most outstanding periods in Spanish popular music occurred in the eighties. A younger generation emerged from the Spanish transition to democracy, influenced by other cultural movements in general, especially in music, which were taking place in the USA and the UK. This led to the birth of a countless number of musical bands, for which the cinema brought a significant point of reference and a never-ending source of inspiration. The aim of this research is to analyse these influences.